Librarian Perspectives on Technical Standards at Academic Institutions with Engineering Technology Programs - Margaret Phillips; Erin M. Rowley; Paul McPherson (Issues in Science and Technology Librarianship, 2024)
Technical standards are resources that are important for engineering and engineering technology students due to ABET accreditation requirements and future professional use of the documents. Previous studies have surveyed librarians at Association of Research Libraries (ARL) institutions with engineering programs and librarians at universities with top-ranked engineering programs about standards. This study fills a gap by focusing on librarians at institutions with engineering technology programs. We surveyed 34 academic librarians at institutions with four-year bachelor programs in the disciplines of mechanical engineering technology or electrical and electronics engineering technology to learn about standards access and challenges at their libraries, standards education for students, and librarians’ standards-related professional development experiences and needs. Key findings include: standards access and standards education efforts are skewed towards larger institutions; librarians encounter significant cost challenges in providing standards access; few librarians receive education about standards until moving into their careers; and there is a need for self-paced librarian training materials focused on standards. Further education for librarians about standards and increased standards access has the potential to have a significant impact on many students, given the reach of librarians in their liaison roles.